Oversharing as a digital vulnerability: Cyberbullying experiences of Generation Z Instagram users - Komsiah, Siti; Tarisha, Tarisha; Zulfa, Rahayu (Bricolage : Jurnal Magister Ilmu Komunikasi, 2026)
The rapid development of information and communication technology has significantly transformed patterns of social interaction, particularly through social media platforms. Instagram, as one of the most widely used visual-based social media platforms, encourages users to share personal experiences, emotions, and daily activities openly. While this openness supports self-expression and social connection, excessive sharing of personal information, commonly referred to as oversharing, may increase users’ vulnerability to negative online interactions. This study aims to examine the relationship between oversharing behavior and cyberbullying among Generation Z Instagram users in East Jakarta. The study employed a quantitative approach using a correlational survey method. Data were collected from 100 respondents selected through purposive sampling. The research instrument consisted of a Likert-scale questionnaire measuring oversharing behavior and cyberbullying experiences, which had been tested for validity and reliability. Data analysis included descriptive statistics, a normality test, and Pearson Product Moment correlation. The results show that both oversharing behavior and cyberbullying fall into the moderate to high category. Correlation analysis indicates a strong and significant positive relationship between oversharing behavior and cyberbullying (r = 0.762, p < 0.001). These findings suggest that higher levels of oversharing are associated with increased exposure to cyberbullying among Generation Z Instagram users. The study highlights the importance of awareness regarding self-disclosure practices in digital communication to reduce potential social risks.